Immune Status and Mortality in Smokers, Ex-smokers, and Never-Smokers: The Ludwigshafen Risk and Cardiovascular Health Study. Issue 7 (18th January 2021) - Delgado, Graciela E; Krämer, Bernhard K; März, Winfried; Hellstern, Peter; Kleber, Marcus E; Leipe, Jan
Abstract: Introduction: Elevated leukocyte counts are associated with cardiovascular disease. Smoking induces inflammation and alters levels of leukocyte subtypes. Aims and Methods: Our aim was to investigate the effect of smoking on circulating immune cells and their association with mortality. Lymphocyte subtypes were identified by flow cytometry of fluorescent-labeled cells. We analyzed the association of leukocytes with mortality using Cox regression and assessed their effect on risk prediction based on principle components (PCs) using area under the receiver operating characteristic curve and net-reclassification in 2173 participants from the Ludwigshafen Risk and Cardiovascular Health Study, a prospective case–control study in patients who underwent coronary angiography. Results: The numbers of T cells, monocytes, and neutrophils were higher and natural killer cells were lower in smokers compared with never-smokers. In never-smokers, lymphocyte counts were inversely associated with mortality while a positive association was observed for neutrophils. The neutrophil-to-lymphocyte ratio (NLR) had the strongest association in never-smokers with a hazard ratio (95% confidence interval) of 1.43 (1.26–1.61). No associations were found in smokers. Adding the first five PCs or the NLR to a risk prediction model based on conventional risk factors did not improve risk prediction in smokers, but significantly increased the area under the curve from 0.777 to 0.801 and 0.791, respectively, in never-smokers. Conclusions: Lymphocyte counts were inversely associated with mortality in never-smokers but not in active smokers. Markers of innate immunity, namely total neutrophils and CD11b+/CD18+ and CD31+/CD40− granulocytes, were directly associated with mortality. Adding markers of immune function like PCs or the NLR to basic risk models improved risk prediction in never-smokers only. Implications: Total leukocyte counts were higher in active smokers as compared to never-smokers due to elevated counts of neutrophils and monocytes but declined in ex-smokers with increasing time since quitting. In the never-smokers but not in smokers, lymphocyte counts were inversely associated with mortality while there was a direct association with neutrophils, even after adjustment for conventional cardiovascular risk factors. Adding markers of immune function to basic risk models improved risk prediction in never-smokers only. Our data indicate that smoking status has an important impact on the ability of leukocyte counts to predict long-term cardiovascular outcomes.